Aorto-Right Ventricular Shunt after TAVR: Rare Complication of Common Procedure. (28th September 2017) - Almanfi, Abdelkader; Qurie, Ahmad; Strickman, Neil
Abstract : Background. The primary treatment of symptomatic aortic stenosis is aortic valve replacement. Instead of open chest surgery, transcatheter aortic valve replacement (TAVR) is an alternative intervention for high-risk surgical candidates. Clinical Case. A 92-year-old male presented with progressive exertional dyspnea and recurrent syncopal attacks secondary to severe AS. The patient underwent successful transfemoral TAVR with 29 mm Edwards SAPIEN XT valve. His postoperative course was complicated by aorto-right ventricular shunt. The patient's clinical course was followed up for one year. Conclusion. This case reports the incidence and clinical course of one of the rare complications of TAVR, aorto-right ventricular fistula. Conservative medical management is appropriate in hemodynamically stable patients with this specific complication.